Development оf combined method for predicting the process of the occurrence of emergencies of natural character - Ivanets, Hryhorii; Horielyshev, Stanislav; Ivanets, Mykhailo; Baulin, Dmitro; Tolkunov, Igor; Gleizer, Natalia; Nakonechnyi, Aleksandr (Eastern-European Journal of Enterprise Technologies, 2018)
We developed a combined method for forecasting of the process of occurrence of emergency situations of a natural character. In contrast with other methods, it makes it possible to perform a complex forecasting of emergency situations, both in general and by types, taking into consideration trends of periodic changes in the process. We considered a number of emergencies for a certain period of time as a generalized parameter of the process. Taking into consideration an influence impact of all destabilizing factors, we should present the process in the form of an additive mixture of systematic, periodic, and random components. The systematic component is a polynomial of some degree. We performed detection and assessment of the periodic component based on the statistical criterion, which subordinates to the chi-square distribution. We used the method of group consideration of arguments to forecast the random component. We should carry out forecasting of emergency situations by type by the probabilistic-statistical method of forecasting. The need to develop a combined forecasting method appears is due to that the existing methods for forecasting of emergency situations focus mainly on forecasting of certain types of emergency situations. Existing methods do not solve the problem of complex forecasting of emergency situations. We should also note that the presence of periodic components of an arbitrary form is characteristic for the process of occurrence of natural emergencies. Consideration of such components in the forecasting of emergency situations makes analysis of the processes of occurrence and development of emergency situations deeper. In the process of experimental studies, we found that the use of the combined method makes it possible to perform forecasting of emergency situations at least a year ahead with a relative forecast error of no more than three percent. The combined method combines the regression analysis method, the method of verification of statistical hypotheses and the method of group consideration of argument. This proves usefulness and expedience of the method. That makes it possible to compensate disadvantages of some methods using other methods, which would lead to the improvement of forecast accuracy